TRANSLATION OF METAPHORS BETWEEN UZBEK AND ENGLISH: A COGNITIVE APPROACH - Ugiloy Karimova (International Journal of Literature and Language Studies, 2026)
Metaphor is one of the major means by which people understand abstract experiences. In the process of translation, metaphors often create problems because they involve culturally and cognitively unique ways of thinking. This paper examines metaphor translation between Uzbek and English languages from the perspective of cognitive linguistics. This paper is based on the perspective of conceptual metaphor theory and translation studies. It examines metaphorical phrases to understand how they expose conceptual mappings and how these mappings influence translation decisions. Through qualitative comparisons with literary texts, political discourse, and spontaneous conversations, the paper has identified three major patterns of metaphor translation: conceptual correspondence, conceptual similarity with different imagery, and culture-bound metaphors that demand accommodation. The findings of the paper demonstrate that metaphor translation depends on rebuilding conceptual mappings rather than words. This paper contributes to translation studies by providing a cognitive-functional approach to metaphor translation between Uzbek and English languages.